Bath Abbey
The circular bath, probably a cold plunge bath associated with an adjacent heated room, is contemporary with the large rectangular bath. These establishments, essential to Mediterranean living, were little suited to the English climate, and clearly belong to a foreign culture. Their use was not continued after the decline of Rome, until revived for medical purposes in the medieval period.